Thermal effectiveness comparison analysis on air-based PV/T system with varying top-to-bottom cavity ratios using CFD simulation - Yanuariska, Nabil Putra Wahyu; Suryaman, Nia Nuraeni; Rajani, Ahmad (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2025)
The development of air-based thermal photovoltaic systems is still challenged in optimizing heat transfer efficiency. One important aspect in this endeavor is to find and improve the cooling channel geometry design. To address this, this study aims to evaluate the effect of several variations of upper and lower cavities on the performance of dual-pass PV/T systems using a computational fluid dynamics (CFD) simulation approach. Four geometry ratio configurations (1:1, 1:4, 2:3, and 3:2) were analyzed based on turbulence intensity, effective thermal conductivity, and air temperature output. The investigation results show that the 3:2 configuration excels in several parameters. The findings highlighted that the 3:2 geometry showed improved turbulence generation and heat exchanger efficiency compared to the other shapes. Specifically, the 3:2 geometry generated turbulence intensity reaching 78% compared to the other geometries, which did not even reach 60%. In addition, the 3:2 geometry produces superior effective thermal conductivity and the most uniform heat transfer. Meanwhile, the 1:4 configuration achieved the highest outlet temperature of 29.54°C, making this geometry potentially suitable for solar energy-based drying applications. The investigation results provide practical insights and geometry-based PV/T system design alloys to improve energy efficiency in sustainable thermal applications.